(untitled) (Physical Education, Health and Social Sciences, 2025)
Oxytocin is routinely used during cesarean sections (CS) to promote uterine contraction; however, its administration is associated with hemodynamic changes that may affect maternal outcomes. This study aimed to evaluate the effects of oxytocin on blood pressure and heart rate and identify predictors of hypotension in women undergoing CS. A prospective observational study was conducted on 60 women undergoing elective or emergency CS under spinal anesthesia. Data collected included demographic variables, obstetric history, preoperative vital signs, oxytocin administration details (dose, route, timing), and hemodynamic parameters. Changes in systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) were monitored, along with the occurrence of hypotension, bradycardia, and associated side effects. Chi-square test, one-way ANOVA, and logistic regression analyses were performed to determine significant associations and predictors of hypotension. The majority of participants were aged 26–30 years (33.3%) and had normal weight (41.7%). Oxytocin was administered most commonly via intravenous bolus (41.7%), with 50% receiving it within 5 minutes post-delivery. Hemodynamic changes were noted, with 63.3% showing a decrease in SBP and 70% a decrease in DBP. Hypotension was observed in 41.7% of cases, with most episodes lasting 1–3 minutes (20%). Logistic regression identified obesity (OR=2.5; 95% CI: 1.1–5.8; p=0.03) and oxytocin doses >20 IU (OR=3.2; 95% CI: 1.4–7.5; p=0.005) as significant predictors of hypotension. Side effects occurred in 33.3% of participants, predominantly nausea (13.3%) and headache (11.7%). Oxytocin was considered safe in 83.3% of cases. Oxytocin administration during CS is associated with significant hemodynamic changes, including hypotension and tachycardia. Higher doses and obesity are key predictors of hypotension. Careful monitoring and dose titration are recommended to improve maternal safety.